2006
DOI: 10.1037/0021-9010.91.4.927
|View full text |Cite
|
Sign up to set email alerts
|

Linking proactive personality and the Big Five to motivation to learn and development activity.

Abstract: The authors investigated links between the Big Five, proactive personality, and motivation to learn. Web-based survey data were collected at 2 points in time from 183 employees of a financial services firm. Results showed that proactive personality was, only in part, a composite of Big Five facets, which accounted for 26% of its variance. Structural equation modeling results demonstrated that proactive personality, openness, extraversion, and conscientiousness predicted motivation to learn. In addition, motiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
401
3
20

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 480 publications
(450 citation statements)
references
References 35 publications
26
401
3
20
Order By: Relevance
“…Career initiative involves a variety of activities including career planning, skill development, and consultation with others (Seibert et al, 2001). Proactive people are thought to possess a greater need for achievement (Thompson, 2005) and a higher motivation to learn (Major, Turner, & Fletcher, 2006) and thus are expected to be engaged in activities that promote their career prospect. Evidence shows that individuals who reflect more actively about their career goals and who have a stronger insight in what they want to attain during their career, report a higher level of career satisfaction (De Vos, & Soens, 2008).…”
Section: Occupational Satisfaction As a Mediatormentioning
confidence: 99%
“…Career initiative involves a variety of activities including career planning, skill development, and consultation with others (Seibert et al, 2001). Proactive people are thought to possess a greater need for achievement (Thompson, 2005) and a higher motivation to learn (Major, Turner, & Fletcher, 2006) and thus are expected to be engaged in activities that promote their career prospect. Evidence shows that individuals who reflect more actively about their career goals and who have a stronger insight in what they want to attain during their career, report a higher level of career satisfaction (De Vos, & Soens, 2008).…”
Section: Occupational Satisfaction As a Mediatormentioning
confidence: 99%
“…For example, in a study looking at antecedents for motivation to learn, Major, Turner, and Fletcher (2006) found the following correlations between proactive personality and four of the Big Five personality characteristics: neuroticism (r = -.15), extraversion (r = .20), openness (r = .37), and conscientiousness (r = .15). However, when they regressed proactive personality on each of the factors, they found that the overall set of Big Five factors only explained 26% of the variance of proactive personality, concluding that proactive personality is an independent individual characteristic (Major et al, 2006). Additionally, similar findings were reported by Thomas, Whitman, and Viswesvaran (2010).…”
Section: Proactive Personality Researchmentioning
confidence: 99%
“…Additionally, while much research has shown the link between proactive personality and proactive behaviors, some research has found no relationship between conscientiousness and proactive behaviors (Wanberg & Kammeyer-Mueller, 2000). For example, in a study looking at antecedents for motivation to learn, Major, Turner, and Fletcher (2006) found the following correlations between proactive personality and four of the Big Five personality characteristics: neuroticism (r = -.15), extraversion (r = .20), openness (r = .37), and conscientiousness (r = .15). However, when they regressed proactive personality on each of the factors, they found that the overall set of Big Five factors only explained 26% of the variance of proactive personality, concluding that proactive personality is an independent individual characteristic (Major et al, 2006).…”
Section: Proactive Personality Researchmentioning
confidence: 99%
“…Career initiative involves a variety of activities including career planning, skill development, and consultation with others (Seibert et al, 2001). Proactive people are thought to possess greater need for achievement (Thompson, 2005) and higher motivation to learn (Major, Turner & Fletcher, 2006) Although not much studies could be found studying the relationship between occupational satisfaction and OCC we expect that just as job satisfaction is related to ORC; occupational satisfaction would be related to OCC and would thus provide a mediating mechanism in the linkage between PP and OCC.…”
Section: H2: the Relationship Between Proactive Personality And Affecmentioning
confidence: 99%